Public-private partnership in widening Indonesia’s internet access with the Palapa Ring Project - Taulu, Richard Angelo Nathaniel; Kurniawan, Teguh (Journal of Governance and Accountability Studies, 2025)
Purpose: This study analyzes how well the Palapa Ring project helps provide equal Internet access across Indonesia, especially in the 3T (Frontier, Outermost, and Disadvantaged) regions. It aims to understand the role of policies and regulations in supporting the project's success and ensuring that all citizens have fair access to digital connectivity. Methods: This study used a normative-juridical method with a qualitative approach. It analyzes the laws and policies related to the Palapa Ring Project. Data were collected by reviewing legal documents, government policy reports and academic writings. No field surveys or specific software were used, only a literature review. Results: The study found that The Palapa Ring project has helped expand Internet access in 3T regions through cross-sector collaboration. However, there are still problems related to regulations and supervision that need to be improved to keep the project effective and trustworthy. Conclusion: The project has made progress in increasing digital access in remote areas; however, stronger regulations and better oversight are necessary to maintain and improve its impact. Limitations: This study is limited to analyzing documents and policies; it does not include direct field observations or interviews, which may limit practical insights. Contributions: This study contributes to the discussions on digital equity, public policy, and infrastructure development. This is useful for policymakers, government agencies, researchers, and organizations working on digital transformation, especially in developing countries or underserved regions.